Dari Rumah Persinggahan ke Rumah Ibadah: Sejarah Sosial Keagamaan Masjid Agung Limbungan di Pagar Alam - Noveliani , Elza; Martiansyah, Eggi; Sabariani, Ranti; Hudaidah, Hudaidah; Gerasela, Gerasela (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This study aims to determine how the Limbungan Grand Mosque in Pagar Alam functions as a center for religious, social, and educational activities. This study uses a descriptive qualitative approach with observation, interview, and documentation techniques. The results of the study indicate that mosque management includes planning, organizing, implementing, and supervising which are carried out in a structured manner by the management together with the community. Mosque activities reflect Islamic values ​​that live in the community, such as deliberation, trust, and social responsibility. The Limbungan Grand Mosque is also a continuation of the process of Islam entering Indonesia and Pagar Alam which took place peacefully through trade, preaching, education, and culture. In the context of the Islamization of knowledge, the management of this mosque is not only technical, but also spiritual, because it integrates the principles of modern management with Islamic values. Mosques play an important role in strengthening Islamic identity and building a civilization of a society with noble morals.